Governing for sustainable health: institutional pathways in China's sport and health policy (1949–present) - Luo, Guanqun (Frontiers in Public Health, 2025)
IntroductionSince 1949, China's sport and health policies have evolved from mass-mobilization campaigns centered on “strengthening physical fitness” to a data-driven framework emphasizing “weight management” and cross-sectoral collaboration under the Healthy China 2030 strategy. However, the institutional processes underpinning this transition remain insufficiently understood and rarely subjected to systematic analysis.MethodsGuided by historical institutionalism, this study conducts a discourse analysis of 15 national policy documents issued between 1949 to present. Python-based text segmentation and keyword frequency and co-occurrence analyses were used to trace shifts in governance instruments and institutional layering.ResultsFindings reveal a three-stage trajectory: (1) an initial stage of ideological mobilization (1949–1995) characterized by centralized fitness directives; (2) a second stage (1996–2015) featuring chronic disease prevention, performance-based targets, and provincial pilot programs; and (3) a current stage (2016-present) focused on obesity control, digital health platforms, and real-time multi-level coordination.DiscussionThis path—dependent layering-from campaign rhetoric to target-based planning to data-enabled governance—demonstrates how embedding new health objectives within entrenched institutional routines, while incrementally integrating cross-sectoral data systems, can foster sustainable policy adaptation. These insights offer a practical and transferable model for other middle-income countries pursuing scalable, evidence-informed health governance.